Improvement of Symptoms of Chronic Prostatitis Like Perineal Heaviness and Frequency After Ten Complete Session of per Rectal Infra Red Laser Therapy (Bangladesh Journal of Urology, 2020)
Objective : To observe the improvement of the symptoms of perineal heaviness and frequency after treatment with Magnetic Infra Red Laser therapy in patients of chronic pelvic pain syndrome /Chronic ProstatitisMethods : This study was an observational study done on 30 male patients with age range varied from 30 to 60 years .The study was conducted from 2009 to 2011 in a private medical center at Dhaka city . The MIL-therapy in use has a wave length of 904 nm and a frequency of 3000 Hz. The Laser beam reaches the prostate with a special optical probe. In this study the patient is examined per rectally after doing digital rectal examination with use of gloves and gel. At the beginning we used a “Laser Super Sonic” machine with endorectal optical probe according to Strada. The treatment schedule was one treatment every two days (treatment’s time of 5/10 minutes, wave length 1000 KHz) for a total of 10 applications. After 10 applications patients were asked for follow up and data were collected and analysed.Results : Out of 30 patients of chronic pelvic pain syndrome aged between 30-60 yrs were under treatment with MIL therapy. Among them only 22 patients were with complains of perineal heaviness, 20 patients were cured and 22 patients were with complains of frequency, 20 were cured and 02 were improved after laser treatment . Among 30 cases 23 patients found normal sized prostate and 07 found enlarged prostate on digital rectal examination and on USG findings, 21 were found normal sized , 09 found enlarged sized prostate and 07 patients had increased PVR .Conclusion : Treatment with Magnetic infra red laser therapy (MIL-therapy) gives useful effect on chronic pelvic pain syndrome (CPPS). The following short article gives a very good summary of the benefits of laser therapy and totally cured of symptoms . CPPS , a painful type of Chronic Prostatitis frequently troubles man for years. Among many sign and symptoms of CPPS , like perineal heaviness and frequency were observed and found very good effect after laser therapy.Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.79-82